Microglia convert aggregated amyloid-β into neurotoxic forms through the shedding of microvesicles - Joshi, P; Turola, E; Ruiz, A; Bergami, A; Libera, D D; Benussi, L; Giussani, P; Magnani, G; Comi, G; Legname, G; Ghidoni, R; Furlan, R; et al. (Cell death and differentiation, 2014)
Alzheimer’s disease (AD) is characterized by extracellular amyloid- β (A β ) deposition, which activates microglia, induces neuroinflammation and drives neurodegeneration. Recent evidence indicates that soluble pre-fibrillar A β species, rather than insoluble fibrils, are the most toxic forms of A β . Preventing soluble A β formation represents, therefore, a major goal in AD. We investigated whether microvesicles (MVs) released extracellularly by reactive microglia may contribute to AD degeneration. We found that production of myeloid MVs, likely of microglial origin, is strikingly high in AD patients and in subjects with mild cognitive impairment and that AD MVs are toxic for cultured neurons. The mechanism responsible for MV neurotoxicity was defined in vitro using MVs produced by primary microglia. We demonstrated that neurotoxicity of MVs results from (i) the capability of MV lipids to promote formation of soluble A β species from extracellular insoluble aggregates and (ii) from the presence of neurotoxic A β forms trafficked to MVs after A β internalization into microglia. MV neurotoxicity was neutralized by the A β -interacting protein PrP and anti-A β antibodies, which prevented binding to neurons of neurotoxic soluble A β species. This study identifies microglia-derived MVs as a novel mechanism by which microglia participate in AD degeneration, and suggest new therapeutic strategies for the treatment of the disease.